TAFSIR JILBAB PEREMPUAN PERSPEKTIF ISLAM DAN PSIKOLOGI - Kholifatus Sa’diyah; Sunarto (Institut Kariman Wirayudha Sumenep, 2022)
This research begins with a statement by a role model about the hijab, which then creates a controversy. This statement can be seen in the podcast interview of Dedy Corbuser and Mrs. Sinta Nuriyah on her youtube channel. Apart from these controversies, this study aims to explore further about the meaning of hijab from an Islamic perspective and psychology including, the definition of women's headscarves, the functions and types of hijab for women, the history of the hijab, the views of scholars about the hijab, the hijab from a psychological perspective, and the hijab in a social context and culture. This research was conducted based on the literature by collecting data and information relevant to the topics discussed. The sources are in the form of documents, books, journals, and articles, then reviewed and described descriptively. As a result, the hijab is a cover for the head, neck, and chest that functions as a cover for the genitals, and maintains honor. The legal basis for the hijab is that it is obligatory and not obligatory. From a psychological perspective, the use of the hijab can be seen from the implications that shape a person's behavior, both good and bad.